Energy, carbon dioxide and water use implications of hydrous ethanol production. (15th November 2015) - Saffy, Howard A.; Northrop, William F.; Kittelson, David B.; Boies, Adam M.
Highlights: We use a chemical refinery model and exergy analysis to determine the impact of hydrous ethanol. The process is 70% efficient with 86% of the losses from fermentation, steam generation and drying. We found that producing 86 wt% ethanol is optimal for thermal energy consumption. Hydrous ethanol production can reduce energy costs and emissions by ∼8%. Hydrous ethanol reduces water use by decreasing evaporation in cooling towers. Abstract: Sub-azeotropic hydrous ethanol has been demonstrated as an effective diesel fuel replacement when used in dual-fuel compression ignition engines. Previous studies have also suggested that hydrous ethanol may be more efficient to produce from corn than anhydrous ethanol. In this study, we investigate corn ethanol production from a dry-mill, natural gas-fired corn ethanol refinery, producing ethanol with a range of ethanol concentrations from 58 wt% to 100 wt% to determine the effect on energy use, water consumption and greenhouse gas (GHG) emissions in the refining stage of the corn ethanol lifecycle. A second law (exergy) analysis of anhydrous ethanol refining revealed the overall process to be 70% efficient, whereby 86% of the exergy losses could be accounted for by three processes: fermentation (34%), steam generation (29%) and distiller's grains and solubles drying (23%). We found that producing 86 wt% ethanol is optimal as thermal energy consumption decreases by a maximum of 10% (from 7.7 MJ/L to 6.9 MJ/L). These savings have the potential to reduce energy costs by approximately 8% ($0.34/L) and reduce refinery emissions by 8% (2 g CO2 e/MJ). Production of hydrous ethanol reduced refinery water use due to decreased evaporative losses in the cooling towers, leading to water savings of between 3% and 6% at 86 wt% ethanol.